PERANCANGAN MODEL STRATEGI E-WOM UNTUK PENGEMBANGAN PARIWISATA ALTERNATIF BERBASIS HERITAGE DI DENPASAR - Kadek Ayu Karawistha Puteri; I Nengah Sudipa; Putu Eka Wirawan (CV. Lafadz Jaya, 2026)
The development of heritage tourism has become an important strategy in promoting alternative tourism that is sustainable, authentic, and experience-based. However, despite possessing significant historical and cultural assets, Denpasar City has not yet been widely recognized as a leading heritage tourism destination in Bali. This study aims to analyze the condition and potential of Electronic Word of Mouth (E-WOM) activities and to develop an E-WOM strategy model for supporting heritage-based alternative tourism development in Denpasar City. The research employed a qualitative descriptive approach with a case study design. Data were collected through observations, in-depth interviews, documentation studies, and digital content analysis conducted at five heritage destinations, namely Bali Museum, Jagatnatha Temple, Badung Market, Puputan Badung Square, and Inna Bali Heritage Hotel. Data were analyzed using descriptive qualitative analysis, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM). The findings indicate that E-WOM activities have developed significantly through digital platforms such as Google Reviews, Instagram, TikTok, and YouTube. Nevertheless, these activities remain fragmented and have not successfully established a strong heritage destination image for Denpasar City. The study proposes an E-WOM strategy model consisting of heritage narrative strengthening, digital media optimization, stakeholder collaboration, and integration of heritage destinations into a unified tourism experience. The model is further implemented through a heritage tourism roadmap and heritage tourism package. The study concludes that E-WOM can serve as an effective strategic tool for enhancing destination image, increasing competitiveness, and supporting sustainable heritage tourism development in Denpasar City.